2012
DOI: 10.1155/2012/827480
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Circulating Follicular Helper T Cells in Patients with Rheumatoid Arthritis

Abstract: Follicular helper T (Tfh) cells are recognized as a distinct CD4+ helper T-cell subset, which provides for B-cell activation and production of specific antibody responses, and play a critical role in the development of autoimmune disease. So far, only one study investigated the circulating Tfh cells increased in a subset of SLE patients. Since relatively little is known about the Tfh cells in rheumatoid arthritis (RA) patients, in this study, Tfh-cell frequency, related cytokine IL-21, and transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
197
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 26 publications
16
197
0
Order By: Relevance
“…Another important transcription factor [14]. Serum levels of IL-21 cytokine were found to be elevated in autoimmune thyroiditis and RA patients [31,32]. In our study, not every patient had …”
Section: The Intensity Of Focus Scores In Association With T Fh Cellsmentioning
confidence: 52%
“…Another important transcription factor [14]. Serum levels of IL-21 cytokine were found to be elevated in autoimmune thyroiditis and RA patients [31,32]. In our study, not every patient had …”
Section: The Intensity Of Focus Scores In Association With T Fh Cellsmentioning
confidence: 52%
“…The alteration of T FHC cells has been reported in patients with various autoimmune diseases, such as rheumatoid arthritis, primary Sjogren's syndrome, juvenile dermatomyositis and autoimmune thyroid diseases, where T FHC cells are present at a higher frequency and show positive correlation with serum autoantibody titer in the patients. [52][53][54][55] Overall, these observations suggest an important role for T FHC cells in human autoimmunity. However, it should be noted that although T FHC cells resemble T FH cells in terms of ICOS and PD-1 expression, T FHC cells in SLE patients do not express Bcl6 and IL-21 that are hallmarks of classic T FH cells.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 69%
“…50 Recent studies have further provided clearer evidence on the role of T FH cells in promotion of both systemic and organ-specific autoimmune diseases in humans. [51][52][53][54][55] Simpson et al 51 performed an elegant study investigating the role of T FH cells in patients with SLE and Sjogren's syndrome. They found an overrepresented population of CD4 1 CXCR5 1 T FH cell-like cells in the blood, referred to as circulating T FH (T FHC ) cells, of a subset of the SLE patients (14 out of 46), which expressed ICOS and PD-1 compared with healthy controls.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Tfh cells can enter the follicle and secrete cytokines and other molecules to help the formation of germinal centre (GC), high-affinity long-living plasma cells and memory B cells [15,16]. A previous study has shown a higher frequency of Tfh cells and increased levels of anti-CCP antibodies in patients with new-onset RA [17].…”
Section: Cd27mentioning
confidence: 99%